2020
DOI: 10.1029/2020jf005562
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Hillslope Scale in Responses of Chemical Erosion Rate to Changes in Tectonics and Climate

Abstract: Chemical erosion is of wide interest due to its influence on topography, nutrient supply to streams and soils, sediment composition, and Earth's climate. While controls on chemical erosion rate have been studied extensively in steady-state models, few studies have explored the controls on chemical erosion rate during transient responses to external perturbations. Here we develop a numerical model for the coevolution of soil-mantled topography, soil thickness, and soil mineralogy, and we use it to simulate resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 81 publications
0
10
1
Order By: Relevance
“…Response times in the climatic experiment were longer than those in the tectonic experiment for all variables (Figure 7g–7l). This differs from a similar experiment in Ferrier and Perron (2020) and is likely due to the introduction of more complex topography and different parameter values. The mean (± s.d.)…”
Section: Results: Transient Landscapescontrasting
confidence: 86%
See 3 more Smart Citations
“…Response times in the climatic experiment were longer than those in the tectonic experiment for all variables (Figure 7g–7l). This differs from a similar experiment in Ferrier and Perron (2020) and is likely due to the introduction of more complex topography and different parameter values. The mean (± s.d.)…”
Section: Results: Transient Landscapescontrasting
confidence: 86%
“…Numerical modeling and experimental work have shown that L h is set by the competition between advective fluvial processes and diffusive hillslope processes (Perron et al., 2009; Sweeney et al., 2015). In numerical simulations in Ferrier and Perron (2020), chemical erosion rates took longer to respond to perturbations in landscapes with longer hillslopes. This matches previous modeling of topographic response times of a single hillslope for both linear and nonlinear hillslope sediment transport to changes in bedrock uplift (Fernandes & Dietrich, 1997; Roering et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The soil catena can be understood from the retention and movement of water and chemical elements linked to topography and vegetation (Reuter and Bell, 2001). Recently, Ferrier and Perron (2020) constructed a numerical model for the coevolution of topography, soils and soil mineralogy that allowed them to conclude that the hillslope scale has a critical importance in the response of chemical weathering rates to changes in tectonics and climate. However, most existing soil formation models do not account for hydrology, nor for chemical weathering reactions.…”
mentioning
confidence: 99%